2003
DOI: 10.1076/jcen.25.1.66.13623
|View full text |Cite
|
Sign up to set email alerts
|

Attention in Adult Intracranial Tumors Patients

Abstract: This study investigated the neuropsychological effects of intracranial tumors on attention, prior to irradiation and chemotherapy. Subjects (n = 55) being treated for low-grade, supratentorial brain tumors were administered tests of attention and working memory. We divided the tumor patients into a "superficial" regional group (e.g., gliomas that infiltrate white matter and meningiomas attached to the cortical surface) and classified them into four brain regions: anterior left side, anterior right side, poster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Nonetheless, when objective neuropsychological assessments have been performed in tumor patients (for a review, see Klein et al 83 ), visuospatial, memory, attention, planning, learning, emotional, motivational, and behavioral deficits have regularly been observed after brain surgery. 3,4,11,12,19,29,55,70,74,75,78,82,87,90,91,101,102,108,111,113,125,137,141,142,149,154 Because these postoperative deficits may have consequences for quality of life, they should lead physicians to change awake surgery paradigms to prevent such permanent cognitive impairments. Indeed, it was recently demonstrated that an increase in reaction time on the picture-naming task, even with normal scores, could prevent patients from returning to normal professional activities.…”
Section: Awake Surgery: a Shift From Intraoperative Single-language Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, when objective neuropsychological assessments have been performed in tumor patients (for a review, see Klein et al 83 ), visuospatial, memory, attention, planning, learning, emotional, motivational, and behavioral deficits have regularly been observed after brain surgery. 3,4,11,12,19,29,55,70,74,75,78,82,87,90,91,101,102,108,111,113,125,137,141,142,149,154 Because these postoperative deficits may have consequences for quality of life, they should lead physicians to change awake surgery paradigms to prevent such permanent cognitive impairments. Indeed, it was recently demonstrated that an increase in reaction time on the picture-naming task, even with normal scores, could prevent patients from returning to normal professional activities.…”
Section: Awake Surgery: a Shift From Intraoperative Single-language Mmentioning
confidence: 99%
“…29, 70,75,78,83,100,106,108,114,125,140,142,153 Such findings raise the question whether it is necessary to add complementary intraoperative tasks such as translation, cross-modal visual-verbal judgment tasks, spontaneous speech, social cognition tasks, or even memory-specific tasks to map and preserve these functions. The answer is probably to adapt the selection to the definition of the quality of life at the individual level, on the basis of the patient characteristics discussed above.…”
mentioning
confidence: 99%
“…For instance, some patients demonstrated minor deterioration in attention after resection of parenchymal frontal or precentral tumors [47, 57] and resection of the right prefrontal cortex rather than the left was associated with a selective attentional impairment in Stroop test performance [58]. After resection of the supplementary motor area, patients exhibited impaired procedural learning and agraphia [59, 60].…”
Section: Introductionmentioning
confidence: 99%
“…(6) Executive functions-phonemic word fluency [38]. (7) Frontal Assessment Battery-FAB to assess frontal functionality [39].…”
Section: Other Cognitive Domain-specific Areas Neuropsychological Tesmentioning
confidence: 99%
“…Specific cognitive domain deficits after brain tumor removal were observed in some studies. A study conducted by Goldstein et al [7] reported minimal deterioration in attention after right parenchymal frontal or precentral tumors resection. Another study [8] concluded that right rather than left prefrontal cortex resection was associated with, stroop performance test, selective attentional decline.…”
Section: Introductionmentioning
confidence: 98%